Expression of Erwinia amylovora hrp genes in response to environmental stimuli. - Wei, Z M (1992)
Seven hrp loci that are essential for the hypersensitive reaction elicited by Erwinia amylovora were transcriptionally fused with a derivative of transposon Tn5, containing the promoterless Escherichia coli beta-glucuronidase reporter gene. The seven hrp fusions were used to monitor expression of the hrp loci in vitro and in planta. No significant expression was detected in rich medium for any of the fusions. However, five of them were expressed highly in planta and in inducing medium that contains mannitol, salts, and 5 mM (NH4)2SO4. Expression of these five hrp loci is regulated by ammonium, nicotinic acid, complex-nitrogen sources, certain carbon sources, temperature, and pH. Under well-defined conditions, i.e., in inducing medium, no specific plant components were required for transcriptional activation of the hrp loci. The high levels of expression detected in vitro were comparable to those determined during the development of the hypersensitive reaction in tobacco. Differential levels of expression of the hrp loci occurred in host and nonhost plants. In pear, a host plant, expression of the hrp loci was delayed and greatly reduced compared with expression in tobacco leaves, a nonhost.